Military Strategy in the 21st Century : The Challenge For NATO - Matlary, Janne Haaland (London Hurst & Company, 2022)
What is military strategy today? In an era when European states seek to de-escalate and avoid armed conflict, and where politicians fear the consequences of protracted operations or tactical hazards, does military strategy have any relevance? This is the first volume to examine current military risks and threats for NATO from a military strategy vantage point. Which strategies are needed? Is ways--ends--means thinking possible as a strategic template today? The contributors probe the relative importance, utility and options of military strategy across NATO as it confronts a variety of challenges old and new, as hybrid threats, new nuclear risks and conventional force combine in complex ways. They also examine what military strategy and military integration really mean, when NATO's multilateral framework is being weakened by degrees of self-interest. They analyse the USA's political and military role in Europe, and assess military strategic responses to Russian aggression in Ukraine and the Middle East. Moreover, they study the role of member states' military strategy set against Article 5 and non-Article 5 risks and threats, and explore how European states devise and implement military strategic options. This book makes a clear assessment of political level strategy and its implications for military integration.
Including Notes And Index
Keywords: Strategy--Political aspects -- Conflict management -- North Atlantic Treaty Organization